Phyllolobium chinense Fisch Flavonoids (PCFF) Suppresses the M1 Polarization of LPS-Stimulated RAW264.7 Macrophages by Inhibiting NF-κB/iNOS Signaling Pathway - Fan, Hua; Wu, Qiong; Peng, Longping; Li, Du; Dong, Yidan; Cao, Min; Liu, Ping; Wang, Xu; Hu, Xudong; Wang, Youhua (Frontiers in Pharmacology, 2020)
Background: M1 macrophage plays an important role in inflammatory reactions. In this study, potential anti-inflammatory effect of total flavonoids from Semen Astragali Complanate (Astragalus complanatus flavonoids, ACF) was assessed via Zebrafish acute inflammation model in vivo and LPS-induced inflammatory macrophage (M1 macrophage) model in vitro. Methods: The quality control of ACF was analyzed by HPLC. Anti-inflammatory effect of ACF on the acute injured zebrafish was evaluated by the migration of fluorescence labeled macrophages and neutrophils, and the gene expression of inflammatory factors. In addition, the anti-inflammatory mechanism of ACF was investigated by the related gene expression and related signaling pathway regulation of pro-inflammatory mediators in LPS-induced M1 RAW264.7 macrophage. Results: ACF markedly suppressed macrophage and neutrophil migration and iNOS gene expression in acute injured zebrafish with tail-cutting. ACF significantly inhibited NO overproduction and iNOS gene overexpression in LPS-sitimulated M1 pro-inflammatory RAW264.7 macrophages. What’s more, ACF could evidently decrease p65 protein production, but had no effect on the production of P38, JNK and ERK1/2 proteins. Conclusion: ACF have a remarkable inhibitory effect on the inflammatory response in acute injured zebrafish and LPS-stimulated RAW264.7 macrophage. The pharmacological mechanism may be related to the regulation of NO overproduction and the inhibition of NF-κB/iNOS signaling pathway.